2013
DOI: 10.1158/1078-0432.ccr-13-0489
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Response to Bevacizumab in Ovarian Cancer: A Panel of Potential Biomarkers Informing Treatment Selection

Abstract: Purpose: The aim of this study was to identify and validate novel predictive and/or prognostic serum proteomic biomarkers in patients with epithelial ovarian cancer (EOC) treated as part of the phase III international ICON7 clinical trial.Experimental Design: ICON7 was a phase III international trial in EOC which showed a modest but statistically significant benefit in progression-free survival (PFS) with the addition of bevacizumab to standard chemotherapy. Serum samples from 10 patients who received bevacizu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 50 publications
0
46
1
Order By: Relevance
“…The three proteins with isoforms that were both up-and down-regulated are depicted in blue. Three apparently highly connected clusters constituted by ribosomal proteins(1), ribonucleoproteins(2), and members of the proteasome complex(3), are highlighted. and the third (cluster 3) contains members of the proteasome complex (PSMB5, PSMC2, PSMC3, PSMD5, PSMD7).…”
mentioning
confidence: 99%
“…The three proteins with isoforms that were both up-and down-regulated are depicted in blue. Three apparently highly connected clusters constituted by ribosomal proteins(1), ribonucleoproteins(2), and members of the proteasome complex(3), are highlighted. and the third (cluster 3) contains members of the proteasome complex (PSMB5, PSMC2, PSMC3, PSMD5, PSMD7).…”
mentioning
confidence: 99%
“…This is probably also true for angiogenesis inhibitors where patients' tumors have shown differing profiles of responsiveness. The reason for the differences is far from clear and the predictive value of angiogenic markers informing of treatment response is debated [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Collinson et al [33] demonstrated that a signature of four serum proteomic biomarkers (mesothelin, fms-like tyrosine kinase-4, α 1 -acid glycoprotein, and CA125) was able to predict benefit from bevacizumab in a cohort of patients from the ICON7 study. The predictive ability was less strong in a second cohort from the same study, but patient numbers were small and it is likely that the validation analysis was underpowered.…”
Section: Prediction Of Responsementioning
confidence: 99%